UPAYA GURU IPS DALAM MENUMBUHKAN SIKAP GOTONG ROYONG MELALUI PEMBELAJARAN INTERAKSI SOSIAL DI KELAS VIII SMP AR-RAHMAN (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the suboptimal implementation of the value of mutual cooperation (gotong royong) among eighth-grade students at SMP Ar-Rahman, despite the school’s vision and mission emphasizing the importance of togetherness and collaboration. In practice, individualistic attitudes, low participation in group work, and a lack of awareness in engaging in cooperative activities within the school environment are still observed. Social Studies (IPS), particularly in the topic of social interaction, has significant potential as a medium to instill these values; however, its implementation tends to focus more on cognitive aspects and has not yet optimally addressed character development. This study aims to describe the efforts of Social Studies teachers in fostering mutual cooperation through social interaction learning and to identify the supporting and inhibiting factors in the process. This research employs a qualitative approach with a descriptive method. The subjects of the study include Social Studies teachers and eighth-grade students of SMP Ar-Rahman. Data were collected through observation, interviews, and documentation, and analyzed interactively through data reduction, data display, and conclusion drawing. The results show that teachers’ efforts to cultivate mutual cooperation are carried out through the implementation of group learning methods, discussions, and collaborative assignments that connect social interaction material with students’ real-life experiences. However, the implementation is not yet fully optimal due to several obstacles, such as low student participation, differences in student characteristics, and individualistic learning habits. Supporting factors include the school’s commitment to the value of mutual cooperation and the teacher’s role as a learning facilitator. Therefore, it is necessary to strengthen more contextual, participatory, and reflective learning strategies so that the value of mutual cooperation can be more effectively internalized within students.